Comparison of the predictive capacity of the Alvarado and AIR scores in the diagnosis of acute appendicitis: A prospective study - L.M. Sanabria-Arévalo; L.C. Domínguez-Torres; J. Kock; J.D. Lotero; J.C. Gómez-Cáceres; E. Tuta-Quintero (Revista de Gastroenterología de México (English Edition))
Introduction and aims: Acute appendicitis stands out as one of the most frequent surgically-treated diseases. Risk scales for acute appendicitis, such as the Alvarado and AIR scoring systems, show good diagnostic yield. The aim of our study was to compare the predictive capacity between the Alvarado and Air scores in the diagnosis of acute appendicitis. Methods: A cross-sectional study was conducted on patients that underwent appendectomy due to suspected acute appendicitis, confirmed by histopathology. The predictive capacity of the Alvarado and Air scores was evaluated through an ROC curve analysis, determining the area under the ROC curve. The STROBE checklist was utilized. Results: A total of 358 patients with clinical suspicion of acute appendicitis were included, 51% of whom were men (183/358). Median patient age was 36 years (IQR: 24−46). The ROC curve of the Alvarado score was 0.767 (95% CI: 0.716−0.818), and with a cutoff point of 0−4, had 78% sensitivity and 84% specificity. The AIR score had a ROC curve of 0.741 (95% CI: 0.691−0.788), and with a 0−4 cutoff point, 87% sensitivity and 56% specificity. There was no statistically significant difference between the two scores (p = 0.266). Conclusion: The Alvarado and AIR scores have a similar predictive capacity for acute appendicitis. The low cutoff points of the risk scales are related to greater diagnostic sensitivity of the disease. Resumen: Introducción y objetivo: La apendicitis aguda destaca como una de las patologías quirúrgicas más frecuentes. El uso de escalas de riesgo para la apendicitis aguda como la escala de Alvarado y AIR muestran un bien rendimiento diagnóstico. El objetivo del artículo es comparar la capacidad predictiva de las escalas de Alvarado y AIR en el diagnóstico de apendicitis aguda. Métodos: Estudio de corte transversal con pacientes sometidos a apendicectomía por sospecha clínica de apendicitis aguda, se confirmó el diagnostico por histopatología. Se evaluó la capacidad predictiva de las escalas Alvarado y AIR mediante análisis de ROC determinando el área bajo la curva (curva ROC). Este estudio utilizo la lista de verificación STROBE. Resultados: Se incluyeron 358 pacientes con sospecha clínica de apendicitis aguda, el 51% eran hombres (183/358) y la mediana de edad fue 36 años (RIC:24−46). La curva-ROC de la escala de Alvarado fue 0.767 (ICdel95%:0.716−0.818), y con un punto de corte de 0 a 4 mostró una sensibilidad de 78% y especificidad de 84%. La escala AIR mostró una curva ROC de 0.741 (IC del 95%: 0.691−0.788), y con un punto de corte de 0 a 4 mostro una sensibilidad de 87% y especificidad de 56%. Al comparar ambas escalas, no se observó una diferencia significativa (p = 0.266). Conclusión: Las escalas de Alvarado y AIR muestran una capacidad predictiva similar para la apendicitis aguda. Los puntos de corte bajos en las escalas de riesgo se relacionan con una mayor sensibilidad diagnóstica de la enfermedad.